Hubungan Pemberian Obat Anti Tuberkulosis (OAT) dengan Kadar Asam Urat - Setiawan, Ivan; Setijadi, Ana Rima; Sari, Yulia (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Multidrug tuberculosis treatment which is a long term medication often causes various side effects. One of them is an increase of uric acid level. This study aims to determine the correlation between tuberculosis treatment administration and uric acid level. Methods: This study used cohort method with one group before and after intervention design. A total of 30 tuberculosis patients who were admitted to Center of Lung Health Society Surakarta between April and August 2013 were taken as samples by consecutive sampling method. Criteria of sampling are pulmonary tuberculosis patients who is planned to get rifampisin, isoniazid, pirazinamid, and ethambutol for more than 4 weeks, aged over 18 years old, and had given informed consent. In this study we excluded pulmonary tuberculosis patients who also had liver or renal disorders, had suffered from hyperuricemia or took drugs for decreasing uric acid level, or had hypertension. The measurements of uric acid level was collected before the treatment and more than one month after the treatment. Data were analyzed by paired t test (α = 0,05). Results: The average uric acid level of 30 patients before treatment was 4.68 ± 1.12 mg/dL, while the average uric acid levels after treatment was 8.56 ± 2.21 mg/dL, which was significantly higher than pretreatment (p=0.001). During treatment, hyperuricemia (uric acid level > 7 mg/dL) was reported in 73.33% (22/30) of patients and two patients had arthralgia. Conclusions: Tuberculosis treatment administration may affect uric acid level. Hiperuricemia was reported in 73.33% of patients who receive tuberculosis treatment. Keywords: tuberculosis treatment, uric acid level, tuberculosis